Rural settlement in Britain - Roberts, Brian K., author.
1 online resource (221 pages)
Keywords: Rural Settlement in Britain (1977) examines the roots of rural settlements prior to the Domesday Book of 1086 and their evolution and changes up to the twentieth century. It looks at the impact of varied environmental, social and economic forces upon settlement and analyses the key questions and models applicable to each particular village. Three systematic themes are closely studied - the forces affecting settlement patterns, the development of village plans, and hamlet and farm settlements.